Interviewing persons with mental illness charged with murder or attempted murder: a retrospective review of police interviews. Issue 6 (2nd November 2019) - Clugston, Bobbie; Green, Bob; Phillips, Jane; Samaraweera, Zara; Ceron, Carolina; Gardner, Cameron; Meurk, Carla; Heffernan, Ed
Abstract : Individuals with a mental illness may be particularly vulnerable during police interviews. Assessing fitness for police interview is vital for ensuring procedural fairness. This article reports the findings of a retrospective review of 31 police interviews of mentally ill persons charged with murder ( n = 18) or attempted murder ( n = 13) who appeared before the Queensland Mental Health Court. Police interviews were conducted for all murder and 50% of attempted murder cases. Possible or overt mental illness symptoms were present in all interviews. Symptoms of mental illness were pervasive in 36.7% of interviews, intermittent in 43.3% of interviews and seldom in 20% of interviews. Support persons were present for 9.7% of interviews, and legal representation was not present for any interview. These findings highlight the need to enhance access to support persons during interviews. Intersectoral collaboration between mental health services, forensic medical officers, police, public guardians and the legal sector is needed.